REGULAR USE OF MILK AND DAIRY PRODUCTS, AND ITS INFLUENCE ON BONE MINERAL DENSITY IN CHILDREN: SYSTEMATIC REVIEW - R.T. Saygitov (Вопросы современной педиатрии, 2008)
This article is dedicated to the analysis of randomized controlled trials, studying influence of milk and diary products (yoghurt, cheese), including fortified with calcium ones, on bone mineral density (BMD) in children. It was shown that addition of such products to the dietary intake of children and adolescents in 9–24 months leads to additional increase of BMD. This property expressed in fortified foods more then in milk in usual (habitual) quantity. In conditions of optimal nutrition, while physiological needs of child's organism in calcium is provided owing to regular use of diary products, a necessity of addition of complementary doses of this macro element to the dietary intake is not proved. Besides, the data from controlled studies showed that adherence of children to some diary products (fortified cheese, for example), is inadequately low. Use of milk, including aromatized one, and yoghurt, allows considerable increasing of compliance. It's important for forming of wholesome nutritive preferences and habits in children.Key words: children, milk, diary products, calcium, bone mineral density.